(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Automation, telemechanics, and signaling systems are among the most important technical components of modern transportation networks. These systems ensure safe train movement, improve operational efficiency, and reduce the possibility of human error. The integration of automated control technologies has significantly transformed railway transport management. This article examines the concept, structure, functions, and importance of automation, telemechanics, and signaling system complexes in transport operations. The study highlights their contribution to transportation safety, traffic control, and operational reliability.